The Impact of Fed Interest Rate Fluctuations on Capital Outflows and the Stability of Indonesia's Capital Market - Retnoning Ambarwati; Nandu Saprudin (PT. Anagata Sembagi Education, 2025)
This study examines the impact of Federal Reserve (The Fed) interest rate fluctuations on capital outflow and the stability of the Indonesian capital market using a quantitative approach with Structural Equation Modeling–Partial Least Squares (SEM–PLS). Monthly data from 2014 to 2024 were analyzed to test causal relationships among the constructs. The results indicate that The Fed’s interest rate fluctuations have a significant positive effect on capital outflow and a significant negative effect on capital market stability. Capital outflow also shows a significant negative effect on market stability. The model reveals that The Fed rate fluctuations explain 46.2 percent of the variance in capital outflow and, together with capital outflow, explain 51.8 percent of the variance in market stability. These findings confirm that global monetary dynamics exert a substantial influence on Indonesia’s capital market. This study provides important implications for regulators and market participants in designing risk mitigation strategies against external shocks.